A search for heavy stable and long-lived squarks and sleptons in e(+)e(-) collisions at energies from 130 to 183 GeV - Abreu, P; Adam, W; Adye, T; Adzic, P; Aldeweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; Amato, S; et al. (1998)
A search for stable and long-lived heavy charged particles used the data taken by the DELPHI experiment at energies from 130 to 183 GeV. The Cherenkov light detected in the Ring Imaging Cherenkov Detector and the ionization loss measured in the Time Projection Chamber identify heavy particles from masses of 2 to nearly 89 GeV/c2. Upper limits are given on the production cross-section and masses of sleptons, free squarks with a charge of q = ± 2/3e and hadronizing squarks. © 1998 Elsevier Science B.V. All rights reserved.